From pilot project to system solution: innovation, spread and scale for health system leaders. Issue 3 (27th September 2018) - Shaw, James; Tepper, Joshua; Martin, Danielle
Abstract : Promoting the scale and spread of effective health innovations requires dedicated action from health system leaders. In order to maximise the effects of leadership strategies to promote the spread and scale of health innovations, conceptual clarity and well-defined strategies are essential. In this commentary, we propose definitions of the concepts of 'innovation', 'spread' and 'scale', and explain how these concepts can be used by health system leaders to generate interest, excitement and commitment for specific innovations from a broad community of stakeholders. We then outline two strategies from the community organising literature that leaders can use to promote spread and scale.